Abstract TP8: Gender Differences in Intracranial Aneurysms - Uchida, Kazutaka; Matsukawa, Hidetoshi; Sowlat, Mohammad-Mahdi; Elawady, Sameh S; Alawieh, Ali; Jabbour, Pascal M; Mascitelli, Justin; Levitt, Michael; Cuellar, Hugo; Samaniego, Edgar A; Kan, Peter; Moss, Mark; et al. (Stroke, 2024)
Background: Some studies have shown that females had a poorer prognosis after endovascular treatment for ruptured intracranial aneurysm than males. However, data has been sparse regarding differences in the periprocedural and perioperative complication rates with ruptured and unruptured intracranial aneurysms. Methods: This retrospective cohort study used data from the Stroke Thrombectomy and Aneurysm Registry, a database of 9 institutions in the United States, Europe, and Asia. The study presented intracranial aneurysms after microsurgical and/or endovascular treatment from January 1, 2013 to December 31, 2022. The primary outcome was the incidence of periprocedural cerebral infarction. Secondary outcomes were periprocedural intracranial hemorrhage, periprocedural mortality, perioperative vasospasm, and functional outcome at 90 days after the procedure. Results: Among 3342 aneurysm patients, 2447 were female and 857 were male, mean age in females and male were 59.6 and 57.1. Current smoker, family history of aneurysm, and ruptured aneurysm were observed in 23.5% vs 35.7 %, 10.8 % vs 5.7%, and 28.2% vs 40.5% of female and male patients, respectively. In female patients, internal carotid artery aneurysms were more commonly observed (31.1% vs 17.3%), however, anterior cerebral artery aneurysm were less commonly observed (18.5% vs 33.8%) compared to male patients. Periprocedural cerebral infarction rate was lower in females than males (2.4% vs. 4.4%; P= 0.002). The adjusted odds ratio of primary outcome of female to male was 0.72 (95% CI, 0.46 - 1.12). Incidence of periprocedural Intracranial hemorrhage and periprocedural mortality, perioperative symptomatic vasospasm, and functional outcome were similar in both groups. In this analysis, periprocedural cerebral infarction due to microsurgical treatment occurred frequently in the male patients, while incidence in endovascular treatment was similar in both groups (interaction P = 0.005). Conclusions: This large multicenter registry of patients undergoing intracranial aneurysm treatment found that female patients were not at increased risk of perioperative complications.